Comparison of coronal microleakage of resin modified glass ionomer and composite resin as intra-orifice barriers in internal bleaching - Mehrdad Barekatain; Maryam Zare jahromi; Salma Habibagahi (Babol University of Medical Sciences, 2016)
Introduction: Internal bleaching is a treatment option for wightening endodontically treated discolored teeth. Cervical resorption is one of the side effects of this method.The aim of this study was to compare the sealing ability of resin composite and light-cured resin modified glass ionomer (RMGI) as intra-orifice barriers in internal bleaching. Materials &Methods: In this study, 34 single-canal anterior teeth were used. All samples were endodontically prepared and divided into two experimental groups (n=12) and two control groups (n=5). In the experimental groups, Gutta-percha was removed up to 3 mm below the cemento enamel junction (CEJ). RMGI and composite resin was placed over gutta-percha in the experimental groups up to the level of CEJ. After 24-hours incubation period, the bleaching agent (a mixture of sodium perborate and 30% hydrogen peroxide) was placed in the access cavities. The bleaching agents were replaced every 3 days over 9 days. Then, the access cavity was filled with 2% methylene blue for 48 hours. All samples were longitudinally sectioned and the dye penetration range was evaluated using stereomicroscope. Data was statistically analyzed by using T-student test and variance analysis. Results: The microleakage in RMGI group was 0.945mm and in composite resin group was 0.641mm. Statistically, no significant difference was observed in microleakage between the experimental groups (p=0.121). Conclusion: Both materials can be applied as the intra-orifice barriers for internal bleaching.